Magang Kerja: Software Engineer Pada PT. Weefer Indonesia - Suryani Huang; Yefta Christian (National Conference for Community Service Project (NaCosPro), 2023)
Community service activities are an important part of bridging the academic world with the outside world. One form of this service is an apprenticeship in a company. This internship activity is also supported by the Merdeka Learning - Merdeka Campus (MBKM) program. Through this MBKM program, the author had the opportunity to do a direct work internship at PT. Weefer Indonesia. Through this opportunity, the author did an internship as a software engineer in a team at a partner company. Using the Agile Scrum method, the authors developed a Product Lifecycle Management (PLM) system with the team. The results of system development will be carried out by a testing process up to the hosting process on a live server so that it can be used by customers. With this internship activity, the author gets a lot of new experience as a software engineer at partner PT. Weefer Indonesia.